Tourism as a propelling factor for the inclusion of ecosystem services value in public policies. The case of the mariposa monarca bio reserve, Mexico - Ortega Cabrera, Verónica (2017)
Mexico's natural wealth positions it among the five most diverse countries in the planet (Semarnat, 2000), committing it to the development of public policies and systematic actions aimed at protecting and preserving species and habitats. Within this context, the Monarch Butterfly Biosphere Reserve, located in the states of Michoacan and Mexico, face great challenges while attempting to protect the plant and animal species which characterize this area, that is to say, those that are part of the Monarch Butterfly (Danaus plexippus) environment, particularly because of tourism, since there are several walkways within the reserve. In light of countless pressures from the region ́s social stakeholders, we propose that an analysis be carried out on the direct and indirect benefits derived from the ecosystemic services, specifically those that are pertinent to tourism, in order to include them in public policies.